The Effects of Installation Procedure on Bond Characteristics of Fully Grouted Rock Bolts - Ma, Shuqi (2018)
The bond characteristics of fully grouted rockbolts installed in steel tubes were investigated by bolt push tests. Steel tubes were inserted in a mine roadway roof to represent the confinement of rock boreholes. Rockbolts were installed in tubes using the installation technique of Australian underground mines. These tubes, with rockbolts inside, were retrieved from the field and brought back to the laboratory to be cut into 100-mm sections, which were then push tested. It was found that each bolt section had a distinct load-displacement profile, and that bond strength varied significantly along the bolt length. The factors influencing the bond strength of rockbolts were identified. The influence of the installation procedure on the bond strength of bolts in tubes was investigated.